(untitled) (Research, Society and Development, 2020)
This article aimed to compare public health policies directed at the population of transsexuals and transvestites, in Brazil and Argentina, in the care provided by public health systems, focusing on the principle of human dignity. The applied methodology is based on a constructionist stance with epistemological support from the theory of social arenas through the concept of social networks, based on the theories developed by Norman Daniels, John Rawls and Judith Butler. The results show Brazil as a country that produces a normative discourse about trans people, and has the LGBTQI+ social movement as its main ally in influencing the development of new public policies. Argentina, in turn, enables the pluralization of trans identities and allows for greater subject autonomy.